Cystatin C and renal function in pediatric kidney transplant recipients - Franco,M.C.P. (2009)
In clinical practice, the glomerular filtration rate (GFR) is often determined with serum creatinine. However, studies have shown cystatin C to be a better parameter for the diagnosis of impaired renal function. We compared GFR estimated by plasma cystatin C with GFR estimated by serum creatinine in a sample of 50 pediatric renal transplant recipients and 24 healthy children. The correlation between GFR estimated by serum creatinine and by cystatin C was significant (r = 0.75; P < 0.001, Person’s correlation); however, in pediatric kidney transplant recipients, the GFR was 6.7 mL/min lower when determined using cystatin C rather than serum creatinine. Moreover, using GFR estimated by cystatin C we found that 42% of the pediatric kidney transplant recipients had an estimated GFR <60 mL·min-1·1.73 (m²)-1, whereas when GFR was estimated by the serum creatinine formula only 16% of the children had values below this cutoff point indicative of chronic kidney disease (P < 0.001). We conclude that, in pediatric kidney transplant recipients, estimation of GFR yields lower values when cystatin C is used rather than serum creatinine.